Partially recrystallized microstructures expand the strength-toughness envelope of CrCoNi medium-entropy alloy - Connor E. Slone; Veronika Mazánová; Punit Kumar; David H. Cook; Milan Heczko; Qin Yu; Bryan Crossman; Easo P. George; Michael J. Mills; Robert O. Ritchie (Communications Materials)
Abstract Engineering materials exhibit an undesirable tradeoff between strength and resistance to crack propagation (fracture toughness). Here we demonstrate how this tradeoff can be circumvented by thermo-mechanical processing that produces a partially recrystallized, heterogeneous microstructure. An equimolar CrCoNi alloy was forged at room temperature (298 K) to produce high densities of three-dimensional crystallographic defect networks. Post-deformation heat treatments caused localized recrystallization that resulted in a bimodal microstructure with hard, non-recrystallized grains and soft, recrystallized grains. In this condition, the yield strength at 298 K is 2.75x the values previously obtained for the same alloy in the fully recrystallized state while the fracture toughness remains the same. The yield strength is further enhanced at 77 K without compromising the fracture toughness. This outstanding strength-toughness combination at 77 K exceeds those reported for other metallic materials and appears to result from the composite nature of the microstructure with non-recrystallized grains providing strength and recrystallized grains enabling plasticity that dissipates stresses during crack propagation. Our findings indicate that by tuning the degree of recrystallization through thermomechanical processing techniques, it will be possible to further expand the envelope bounding the strength and toughness of a range of structural metals at engineering component scales.